Deoxycholic acid activates epidermal growth factor receptor and promotes intestinal carcinogenesis by ADAM17‐dependent ligand release. Issue 9 (29th June 2018) - Dong, Wenxiao; Liu, Li; Dou, Yan; Xu, Mengque; Liu, Tianyu; Wang, Sinan; Zhang, Yujie; Deng, Baoru; Wang, Bangmao; Cao, Hailong
Abstract: High fat diet is implicated in the elevated deoxycholic acid (DCA) in the intestine and correlated with increased colon cancer risk. However, the potential mechanisms of intestinal carcinogenesis by DCA remain unclarified. Here, we investigated the carcinogenic effects and mechanisms of DCA using the intestinal tumour cells and Apc min/+ mice model. We found that DCA could activate epidermal growth factor receptor (EGFR) and promote the release of EGFR ligand amphiregulin (AREG), but not HB‐EGF or TGF‐α in intestinal tumour cells. Moreover, ADAM‐17 was required in DCA‐induced promotion of shedding of AREG and activation of EGFR/Akt signalling pathway. DCA significantly increased the multiplicity of intestinal tumours and accelerated adenoma‐carcinoma sequence in Apc min/+ mice. ADAM‐17/EGFR signalling axis was also activated in intestinal tumours of DCA‐treated Apc min/+ mice, whereas no significant change occurred in tumour adjacent tissues after DCA exposure. Conclusively, DCA activated EGFR and promoted intestinal carcinogenesis by ADAM17‐dependent ligand release.